Sur les lois asymptotiques de distribution des fonctions arithmétiques additives - Kubilius, J. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. Кубилюс. Об асимптотических законах распределения аддитивных арифметических функцийJ. Kubilius. Adityvinių aritmetinių funkcijų asimptotinių pasiskirstymo dėsnių klausimu